The Efficacy of Azelaic Acid 20% Cream in the Treatment of Scalp Alopecia Areata - Mudheher Salih; Dindar Qurtas (المجلة العراقية للصيدلة, 2022)
Introduction: Alopecia areata is a common, inflammatory, non-scarring type of hair loss that affects persons of both sexes and all age groups, with prevalence in the general population of approximately 0.1–0.2%. It is characterized by variable clinical presentations, ranging from single or multiple well-circumscribed patches of hair loss to extensive involvement with complete absence of body and scalp hair. Alopecia areata is an autoimmune disease of the hair follicle. Its pathogenesis is associated with loss of follicular immune privilege and T-cell mediated inflammatory response, leading to interruption of the hair growth cycle. The diagnosis of alopecia areata is usually based on clinical manifestations in addition to using   severity of alopecia tool score. Currently, there is no treatment for alopecia areata approved by the US Food and Drugs Administration. However, several treatment modalities for alopecia areata have been introduced with variable outcomes. Although topical and systemic immunomodulators are the mainstay options, there is still a lack of high-quality randomized controlled trials supporting these treatment modalities.  Topical Corticosteroids are considered the first-line therapy for patch-type alopecia areata. Azelaic acid is a dicarboxylic acid, derived from the fungus Pityrosporum ovale and is regarded as an effective topical therapy for patchy alopecia areata. Aim of study: The present study aims to measure the efficacy of topical azelaic acid cream 20% in the treatment of alopecia areata. Patients and Methods: The all 30 patients were collected from Erbil Dermatology Teaching Center. They were divided into two groups: group A includes fifteen   patients on topical clobetasol propionate 0.05% cream; group B includes fifteen patients on topical azelaic acid 20% cream. Both treatment groups were followed up for period of around twelve weeks with monthly check up visits. Both drugs were applied topically once daily at night. Results: the comparison between the baseline and 12 weeks visits for each study group concerning severity of alopecia tool score shows that the mean of the score for both groups at 12 weeks visit is lower than that of baseline visit in a statistically significant way (group A, p=0.007, group B, p=0.036). Conclusions: This study showed that topical azelaic acid cream 20% has an acceptable efficacy in comparison to topical clobetasol ointment 0.05% in the treatment of localized alopecia areata of scalp and can be considered as a therapeutic option for this condition.